Detection of Listeria monocytogenes in Pasteurized Milk Sold in Bogor and Its Relationship with Human Health - AGATHA WINNY SANJAYA; MIRNAWATI SUDARWANTO; KIBUUKA ROBERT (Indonesian Society for microbiology, 2009)
Many countries have established a zero tolerance policy, under which ready-to-eat foods are contaminated with Listeria monocytogenes at a detectable level. The research was done in two parts. The first part was to qualitatively identify the presence of L. monocytogenes in pasteurized milk (n=32 samples) sold in different supermarkets in Bogor. The method was adopted from the Bacteriological Analytical Manual/Food and Drug Administration. All samples tested resulted negative to L. monocytogenes. The second part of the research was to evaluate the growth of L. monocytogenes in sterilized milk stored in an incubator set at 4oC and monitored for 7 days. The original L. monocytogenes culture at a concentration of 1x109 cfu mL-1 was diluted with buffered phosphate water 0.1% to reach a cell concentration of approximately 1.0 x 102 cfu mL-1. Growth was observed on the first, second, third, fourth and fifth day. On the sixth and seventh day, the numbers of colony forming units observed were almost similar (2.5-2.8 x 105 cfu mL-1). A population of 10 cells is sufficient to cause serious listeriosis infection in human.